Predictors of parents' preventive practices toward Hand Foot Mouth Disease at Workplace Child Centre in Pahang, Malaysia - Abd Ghani, Norfarihah; Mansor, Zawiah (Universiti Putra Malaysia Press, 2024)
Introduction: Hand, foot, and mouth disease (HFMD) outbreaks are increasingly occurring in workplace child centres, highlighting the need for preventive measures. Both child centre caregivers and parents play a crucial role in preventing the spread of the disease, as it can be brought from home and quickly transmitted within the premises. Thus, this study aims to determine the level of HFMD preventive practice and the predictors among parents who enrol their children at the workplace child centre in Pahang. Materials and methods: A cross-sectional study was conducted by distributing a self-administered questionnaire to 163 parents who sent their children to workplace child centres selected via stratified random sampling. Validated and reliable questionnaires were used to assess the HFMD level of preventive practice and associated factors. Data were analysed by using SPSS version 28. Multivariate logistic regression was used to determine the predictors of good preventive practices. Results: The majority of respondents showed a good level of HFMD prevention practices (90.1%). Factors associated with HFMD preventive practice level were education level, history of child infected with HFMD and knowledge of HFMD (p<0.05). The predictors of a good level of preventive practices toward HFMD were tertiary education level (AOR = 8.28, 95% CI: 2.308, 20.154) and history of children infected with HFMD (AOR = 5.02, 95% CI: 1.192, 10.133). Conclusion: A high level of preventive practices among parents may contribute to the control and prevention at workplace child centres. Health promotion content may be improved by including parent's experience with HFMD. It is also useful to target health promotion towards parents with lower education levels and those who have never first-hand experience of a child with HFMD.